Systematic review—understanding the barriers and facilitators experienced by healthcare professionals in providing care for tics: a mixed methods systematic review of clinical knowledge, attitudes, and practices - Adam Parker; Blandine French; Madeline J. Groom; Charlotte L. Hall (BMC Medical Education)
Abstract Tic disorders (TDs) have a prevalence of approximately 1%, and while various therapies have demonstrated effectiveness, people with tics and their families report a lack of understanding by healthcare professionals (HCPs). This systematic review included 13 papers featuring HCPs, people with tics, and their families about their experiences of either delivering or accessing care for tics, which were then divided into three themes. The first theme, Need for Education and Effective Implementation, suggested that while HCPs demonstrated good knowledge of tics, patient experiences indicated that this did not always translate to the care they received, potentially due to low confidence and a lack of formal training. The second theme, Misinterpretation, Misdiagnosis and Stigma, suggested that HCPs held incorrect beliefs about tics and would misinterpret tic symptoms, while caregiver responsibility for their child’s tics would both positively and negatively impact care-seeking behaviour, partly depending on their cultural belief system. Finally, the Communication between Healthcare Professionals and Families revealed that poor communication of a tic disorder diagnosis can exacerbate anxiety within the family. The themes of this review were demonstrated universally, demonstrating that HCPs around the world should be encouraged to understand tics and tic disorders confidently to improve the healthcare outcomes and experiences of those living with tics.